2008
DOI: 10.1107/s0108768108021125
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Ga2O3(ZnO)6: a member of the homologous series Ga2O3(ZnO) m

Abstract: The structure of Ga(2)O(3)(ZnO)(6) was determined using single-crystal X-ray diffraction techniques in the space group Cmcm. The metal ion sublattice resembles some of the Zn ions in the wurtzite ZnO structure. The oxygen ion sublattice in Ga(2)O(3)(ZnO)(6) also resembles some of the O ions in ZnO. Structural relationships between Ga(2)O(3)(ZnO)(6) and ZnO are discussed, illustrating the process for obtaining the centrosymmetric Ga(2)O(3)(ZnO)(6) structure from the noncentrosymmetric ZnO. Structures of phases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
45
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 16 publications
3
45
0
3
Order By: Relevance
“…Experimental characterisation using XRD has found that GZO crystallizes in orthorhombic structures with space group Cmcm for n > 1, and the 'normal' cubic spinel structure for m = n = 1. The internal structural parameters (atomic positions) have been reported only for m = 1, n = 1, 6 [103]; however, it is important to note that the atomic number of Ga and Zn differs only by one unit, and hence, XRD alone cannot clearly distinguish between the Ga and Zn site occupation, i.e. it was assumed that Ga atoms occupy specific cation sites, while Zn occupy the remaining sites.…”
Section: Rules Governing Structure Formation Crystalline Multi-componmentioning
confidence: 99%
See 4 more Smart Citations
“…Experimental characterisation using XRD has found that GZO crystallizes in orthorhombic structures with space group Cmcm for n > 1, and the 'normal' cubic spinel structure for m = n = 1. The internal structural parameters (atomic positions) have been reported only for m = 1, n = 1, 6 [103]; however, it is important to note that the atomic number of Ga and Zn differs only by one unit, and hence, XRD alone cannot clearly distinguish between the Ga and Zn site occupation, i.e. it was assumed that Ga atoms occupy specific cation sites, while Zn occupy the remaining sites.…”
Section: Rules Governing Structure Formation Crystalline Multi-componmentioning
confidence: 99%
“…it was assumed that Ga atoms occupy specific cation sites, while Zn occupy the remaining sites. The pioneering work reported by Michiue et al [103] provided a basis for the understanding of the atomic structure of GZO compounds; however, a number of questions remained to be solved at that time.…”
Section: Rules Governing Structure Formation Crystalline Multi-componmentioning
confidence: 99%
See 3 more Smart Citations